The Effect of Visualization Strategies on Writing Explanatory Texts Skill on VIIIth Grade Students of SMP Muhammadiyah 3 Jakarta - Hadi Nugroho; Endry Boeriswati; Reni Nur Eriyani (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This study aims to see the effect of visualization strategies on writing explanatory text skill on VIIIth grade students of SMP Muhammadiyah 3 Jakarta. The method used in this study was an experimental method with a control group pre-post test design. T-test and Fisher's test were used as data analysis techniques in this study. The results of the t-test on the post-test score between the experimental and the control class indicated that the t-test score was 6.99> 2.06 t-table with dk 24. Significant level = 0.05. Because tcount> ttable means H1 is accepted. The results of this study indicated that the application of visualization strategies had an effect on the ability to write explanatory text for VIII grade students of SMP Muhammadiyah 3 Jakarta. The results of the general assessment showed that the organizational structure and reviews had the most dominant increase. From the results above, the visualization strategy can be used as a good strategy in learning to write explanatory text. Besides, as well as can be implied for explanatory text learning material with KD 3.10 “Examining explanatory text in the form of exposure to natural phenomena that are heard or read” and KD 4.10. “Presenting information and data in the form of an explanatory text of the process of an oral and written phenomenon by paying attention to the structure, language elements, or oral aspects”. Keywords: visualization strategy, writing explanatory text skill Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh strategi visualisasi terhadap kemampuan menulis teks eksplanasi siswa kelas VIII SMP Muhammadiyah 3 Jakarta. Metode yang digunakan dalam penelitian ini yaitu metode eksperimen dengan desain penelitian prates dan postes grup kontrol. Uji-t dan uji fisher digunakan sebagai teknik analisis data dalam penelitian ini. Hasil uji-t pada skor postes antara kelas eksperimen dan kelas kontrol menujukan bahwa skor thitung 6,99> ttabel 2,06dengan dk 24. Taraf signifikan = 0,05. Karena thitung > ttabel berarti H1 diterima. Hasil penelitian ini menunjukkan bahwa menerapkan strategi visualisasi berpengaruh terhadap kemampuan menulis teks eksplanasi siswa kelas VIII SMP Muhammadiyah 3 Jakarta. Hasil penilaian menunjukkan bahwa aspek struktur identifikasi umum dan ulasan mengalami kenaikan yang paling dominan. Dari hasil tersebut, strategi visualisasi dapat dijadikan strategi yang baik dalam pembelajaran menulis teks eksplanasi serta dapat juga diimplikasikan untuk materi pembelajaran teks eksplanasi dengan KD 3.10 “Menelaah teks eksplanasi berupa paparan kejadian suatu fenomena alam yang diperdengarkan atau dibaca” serta KD 4.10 “Menyajikan informasi dan data dalam bentuk teks eksplanasi proses terjadinya suatu fenomena secara lisan dan tulis dengan memerhatikan struktur, unsur kebahasaan, atau aspek lisan”. Kata kunci: strategi visualisasi, kemampuan menulis teks eksplanasi